Mean-reversion and structural change in European food prices - Kurmas Akdogan (Central Bank Review (CBR), 2018)
Mean-reversion in unprocessed food prices and beef prices towards the long-run trend is examined for twenty-two European countries, using linear and nonlinear unit root tests. As the argument goes, food prices might display short-term deviations from their long-run values due to disturbances such as changes in climate or speculation; yet, once the impact of these short-lived shocks fade away, the prices convert to the long-run equilibrium level determined by fundamentals. The nonlinear smooth transition framework suggest that the speed of this adjustment might depend on the size and sign of the deviation of prices from their long-run values. The results carry important policy implications regarding the benefits of short-term demand management policies along with structural policies.
Keywords: 330; Food prices; Mean-reversion; Structural break; Nonlinearity